Reducing the Intensity of First Stage Labor Pain through Therapeutic Communication - Fitria, Aida; Suriyani, Elvi; Savitri, Meli; Ningrum, Allania Hanung Putri Sekar (Qualitative and Quantitative Research Center, 2023)
The direct causes of maternal death during childbirth are bleeding, infection, and eclampsia. Within bleeding and infection as causes of death, deaths due to infected abortion and prolonged labor are also included. Meanwhile, one of the causes of prolonged labor is tension and fear, which aggravates labor pain and ultimately slows down the birth of the baby. One method of non-pharmacological pain control is through nursing communication, namely therapeutic communication. This research aims to determine the effect of implementing therapeutic communication in efforts to reduce the intensity of labor pain in the first stage. This research method is an analytical survey method that uses one group pretest-posttest. The total sample was 25 maternal patients giving birth. Data analysis used the paired sample t-test. The study's results showed a significant difference in the intensity of pain in the first stage of labor before and after the therapeutic communication intervention was given. Therapeutic communication can strengthen the relationship between the midwife and the mother in cases of the intensity of first-stage labor pain, increase the mother's understanding, encourage emotional expression, and reduce worry and anxiety. Based on evidence of the effectiveness of research data, this research contributes to recommending therapeutic communication as a non-pharmacological strategy for overcoming tension and fear that aggravate labor pain.